AREAS OF INCREASING THE CAPACITY OF MANAGERS IN STATE ADMINISTRATION BODIES (American Journal of Business Management, Economics and Banking, 2023)
After the independence of the Republic of Uzbekistan, the methods of conducting business activities and managing establishments began to change. Issues such as the economic aspects of introducing corporate governance models, the formation of an effective management system of joint-stock companies (JSC), the principles of management, and the factors influencing its formation have begun to receive attention. After the Republic of Uzbekistan gained independence, the creation of the legal and organizational foundations for the formation of a multi-level economy and competitive environment, which can ensure high rates of economic growth and sustainable development of society, was set as a priority.